GPS/Low-Cost IMU/Onboard Vehicle Sensors Integrated Land Vehicle Positioning System. (6th June 2007) - Gao, Jianchen; Petovello, Mark G.; Cannon, M. Elizabeth
Abstract : This paper aims to develop a GPS, low-cost IMU, and onboard vehicle sensors integrated land vehicle positioning system at low cost and with high (cm level) accuracy. Using a centralized Kalman filter, the integration strategies and algorithms are discussed. A mechanism is proposed for detecting and alleviating the violation of the lateral nonholonomic constraint on the wheel speed sensors that is widely used in previous research. With post-mission and real-time tests, the benefits gained from onboard vehicle sensors and the side slip detection and alleviation mechanism in terms of the horizontal positioning accuracy are analyzed. It is illustrated by all the tests that GPS plays a dominant role in determining the absolute positioning accuracy of the system when GPS is fully available. The integration of onboard vehicle sensors can improve the horizontal positioning accuracy during GPS outages. With respect to GPS and low-cost IMU integrated system, the percentage improvements from the wheel speed sensor are 90.4% for the open-sky test and 56.0% for suburban area real-time test. By integrating all sensors to detect and alleviate the violation of the lateral nonholonomic constraint, the percentage improvements over GPS and low-cost IMU integrated system can be enhanced to 92.6% for open-sky test and 65.1% for the real-time test in suburban area.